2020
DOI: 10.1080/14631369.2020.1775485
|View full text |Cite
|
Sign up to set email alerts
|

Psychological wellbeing in diaspora space: a study of African economic migrants in Hong Kong

Abstract: African migrants in Hong Kong and the rest of Greater China are often confronted with numerous social and economic constraints. Notwithstanding, extant studies have not adequately examined how these challenges affect the psychological wellbeing of Hong Kong's African economic migrants specifically. Using a qualitative research design underpinned by the concept of diaspora space, this article discusses the social aspects of psychological wellbeing among African economic migrants in Hong Kong. Specifically, it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This also shapes Chinese Han perceptions of the African continent and Black racial identity in which they view themselves not as exploiters, but in their ethnocentrism, as benevolent actors in a global racial hierarchy led by the "superior" European and American white race (Dikötter, 1992;1997). In their examination of the well-being of African-Black migrants, Amoah et al (2020) found that negative Chinese attitudes caused psychological distress on Africans through the confusion of their personal and social identity as black people, discrimination, and in the struggle to form enduring relationships with the locals. They also found that the media has also contributed to these negative attitudes by highlighting news reports on drugs, AIDs, illegal immigration, crime, fraud, and other offenses when mentioning African migrants (Li, Ma & Xue, 2009).…”
Section: Chinese Racism Towards the Black Communitymentioning
confidence: 99%
“…This also shapes Chinese Han perceptions of the African continent and Black racial identity in which they view themselves not as exploiters, but in their ethnocentrism, as benevolent actors in a global racial hierarchy led by the "superior" European and American white race (Dikötter, 1992;1997). In their examination of the well-being of African-Black migrants, Amoah et al (2020) found that negative Chinese attitudes caused psychological distress on Africans through the confusion of their personal and social identity as black people, discrimination, and in the struggle to form enduring relationships with the locals. They also found that the media has also contributed to these negative attitudes by highlighting news reports on drugs, AIDs, illegal immigration, crime, fraud, and other offenses when mentioning African migrants (Li, Ma & Xue, 2009).…”
Section: Chinese Racism Towards the Black Communitymentioning
confidence: 99%
“…Nonetheless, research comparing the prevalence of depression in the general population in different countries/region is still evolving. Evidence suggests that prevalence and correlates of depressions and other mental health conditions differ in terms of age, gender, physical health status, socio-economic situation, living circumstances and health-related knowledge (14)(15)(16)(17)(18)(19)(20). In addition, little is known about the association between digital health literacy and mental health.…”
Section: Introductionmentioning
confidence: 99%